Water on Mars: Insights from apatite in regolith breccia Northwest Africa 7034 - Davidson, Jemma (Earth Planet Sci Lett, 2020)
Determining the source of planetary water from the hydrogen isotope compositions of crustal samples is complicated by the overprinting of isotopically diverse source material by geologic and atmospheric processes. As Mars has no plate tectonics, crustal material, which may have isotopically exchanged with the martian atmosphere, is not recycled into the mantle keeping the water reservoirs in the mantle and atmosphere mostly isolated, buffered by the crust. As the only known martian samples that are regolith breccias with a composition representative of the average crust of Mars, Northwest Africa (NWA) 7034 and its paired stones provide an important opportunity to investigate the water content and hydrogen isotope composition of the martian crust. In particular, apatites in distinct clasts as well as the brecciated matrix of NWA 7034 record a complex history including magmatic and impact processes, and exchange with crustal fluids.